2021
DOI: 10.3389/fneur.2021.732176
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation in Non-Brain Injured Patients: A Systematic Review

Abstract: Introduction: Cerebral autoregulation (CA) plays a fundamental role in the maintenance of adequate cerebral blood flow (CBF). CA monitoring, through direct and indirect techniques, may guide an appropriate therapeutic approach aimed at improving CBF and reducing neurological complications; so far, the role of CA has been investigated mainly in brain-injured patients. The aim of this study is to investigate the role of CA in non-brain injured patients.Methods: A systematic consultation of literature was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Ketamine in an acute setting could not impact cerebral autoregulation: a delicate mechanism altered in acute brain injury [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine in an acute setting could not impact cerebral autoregulation: a delicate mechanism altered in acute brain injury [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cases of increased ICP, the self-regulation system and brain compliance maintain intracranial pressure level within physiological limit allowing an adequate cerebral perfusion pressure. In severe TBI, the loss of the cerebral compliance causes intracranial hypertension syndrome and brain herniations [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the application of neuromonitoring tools able to assess CA has been applied in a variety of situations outside the neurocritical care settings. A recent systematic review found 22 articles exploring the role of monitoring CA in the perioperative settings, in ICU patients with sepsis, and in the pediatric population, suggesting that even in patients without brain injury, altered CA may result in increased mortality [ 30 ]. In addition, disturbed CA was found as a common event, as it is reported in about 50% of patients in the general ICU [ 31 ].…”
Section: Discussionmentioning
confidence: 99%